Fiscal policy, monopolistic competition, and finite lives - Ben J. Heijdra; Jenny E. Ligthart (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper studies the short-run, transitional, and long-run output effects of permanent and temporary shocks in public consumption under various financing methods. To this end, a dynamic macroeconomic model for a closed economy is developed, which features a perfectly competitive final goods sector and a monopolistically competitive intermediate goods sector. Finitely lived households consume final goods, supply labor, and save part of their income. Amongst the findings for a permanent rise in public consumption are: (i) monopolistic competition increases the absolute value of the balanced-budget output multiplier; (ii) positive long-run output multipliers are obtained only if the generational turnover effect is dominated by the intertemporal labor supply effect; (iii) short-run out- put multipliers under lump-sum tax financing are smaller than long-run output multipliers if labor supply is elastic; and (iv) bond financing reduces the size of long-run output multipliers as compared to lump-sum tax financing and may give rise to non-monotonic adjustment paths if labor supply is sufficiently elastic and the speed of adjustment of lump-sum taxes is not too high. Temporary bondfinanced fiscal shocks are shown to yield: (i) permanent effects on output; and (ii) negative long-run output multipliers.
Keywords: E12; L16; E63; 330; fiscal policy; output multipliers; Yaari-Blanchard model; overlapping generations; monopolistic competition; love of variety; Finanzpolitik; Multiplikator; Monopolistischer Wettbewerb; Overlapping Generations; Theorie; Finanzierung; Theorie